Detection and phylogenetic analysis of new Iranian isolates of Cucumber mosaic virus on Achillea species - Faezehossadat Abtahi; Mehrnaz Hatami; Hossein Salehi-Arjmand; Majid Mahdiyeh; Razieh Yazdani (Journal of Crop Protection, 2021)
Cucumber mosaic virus (CMV) is one of the most important viruses that globally cause disease outbreaks in horticultural, vegetable, and agronomic crops. To investigate the incidence of viruses infecting Achillea species (yarrows), 350 samples with mosaic, yellowing, and deformation symptoms were collected from different Markazi province locations during the spring seasons of 2017, 2018. CMV infection was detected by using DAS-ELISA. Five samples were selected for phylogenetic studies based on sampling areas and yarrow’s species. A 657 bp fragment of coat protein was amplified using specific primers of CMVCPr and CMVCPf in RT-PCR, cloned and sequenced. Obtained sequences of this study were compared with the retrieved sequences from GenBank. The identities of the CP at the nucleotide and amino acid levels were 95% and 100%, respectively, and are close to other Iranian isolates of CMV. Constructed phylogenetic tree showed that five Iranian isolates from yarrows were placed in the subgroup IB. This finding is the first genetic analysis of CMV from yarrow in Iran.